1888 Id. Sess. Laws 23, An Act Regulating the Use and Carrying of Deadly Weapons in Idaho Territory, § 1 - (:unkn) unknown (General Publisher, 1888)
Prohibited the carry, exhibition, or flourish of any dirk, dirk-knife, sword, sword-cane, pistol, gun, or other deadly weapons. Violators guilty of a misdemeanor, punishable by fine not less than fifty nor more than one hundred dollars, or imprisonment in jail for not less than twenty nor more than fifty days, or both fine and imprisonment.
--
Keywords: CARRY